Adsorption of xylene isomers in MOF UiO-66 by molecular simulation - Miguel Angelo Granato (2014)
This work presents results of molecular simulations on adsorption of mixtures of the four xylene isomers in the porous zirconium terephthalate UiO-66. The grand-canonical Monte Carlo simulations (GCMC) are compared to multi-component adsorption equilibrium data obtained by breakthrough experiments. Four different force fields for the xylenes were evaluated. The simulations confirm that the experimentally observed ortho-selectivity is preferential in relation to the other isomers. Additionally, it was found that there is a competition between the other three isomers (para-xylene, meta-xylene and ethylbenzene) for adsorption in the UiO-66 structure. Molecular simulation is applied as a powerful research tool in predicting adsorption equilibrium properties of potential adsorbent candidates for xylene isomers mixtures that are essential for the development of adsorption based separation processes.